Lead adsorption in lubricant waste using zeolite - Aini Rahmadhaniar; Ratri Ariatmi Nugrahani; Nurul Hidayati Fithriyah; Titik Lestariningsih (Jurnal Rekayasa Proses, 2020)
Lubricant waste is one of the hazardous refuses which are regulated on the limit of lead content according to Government Regulations (Kep-51/MenLH/10/1995). Therefore, it is necessary to research for reducing the lead content. The purpose of this study is to understand the effect of adding adsorbents to decrease lead content in waste of lubricants taken from ships. The waste lubricant was recycled by adsorption using zeolite. Lubricant waste samples of 200 mL each were physically and chemically identified subjected to adsorption process using zeolite adsorbent whose concentrations (%w/w) were varied as follows: 7.5%, 13.25%, 14.25%, 15.75% and 17.5% with stirring speed of 150 rpm and contact time for 60 minutes. The best results were obtained at the adsorbent amount of 26.5 grams (concentration of 13.25%), for which lead content reduction reached 83%. The ANOVA F was obtained to be 13.42, and hence the study concluded that the amount of the adsorbent was related to the decrease in lead content.